2010
DOI: 10.1080/10426500903575409
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of New Dialkyl Benzene-, Biphenyl-, and Naphthalene-bis(α-oxoethanedithioates)

Abstract: Novel arene-bis-and -tris(α-oxoethanedithioate) esters of the benzene, the biphenyl, and, in particular, the naphthalene series were prepared by reaction of the corresponding diazoacetyl or bromoacetyl derivatives with elemental sulfur in the presence of triethylamine in dry DMF, and subsequent direct alkylation of the produced dithiocarboxylate anions. The thiolation reaction of the diazoketones was significantly promoted by the addition of anhydrous calcium chloride (calcium chloride-activated thiolation, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Curiously, while the synthesis of thioamides from thionoesters has been reported extensively, the use of alcohols as nucleophiles for the transesterification of thionoesters is extremely rare. Early research involving transesterification of dithiobenzoyl acetic acid suggested to us that transesterification should provide a straightforward means to rapidly diversify thionoesters. , In addition, exchange reactions with dithioesters and alcohols have been reported. , It was also demonstrated that α-oxo-dithioesters will undergo transesterification yielding thionoesters. , One notable use of this strategy is in the total synthesis of clostrubin, where the resulting thionoester was used in a Barton-Kellogg olefination as a key step in the synthesis …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Curiously, while the synthesis of thioamides from thionoesters has been reported extensively, the use of alcohols as nucleophiles for the transesterification of thionoesters is extremely rare. Early research involving transesterification of dithiobenzoyl acetic acid suggested to us that transesterification should provide a straightforward means to rapidly diversify thionoesters. , In addition, exchange reactions with dithioesters and alcohols have been reported. , It was also demonstrated that α-oxo-dithioesters will undergo transesterification yielding thionoesters. , One notable use of this strategy is in the total synthesis of clostrubin, where the resulting thionoester was used in a Barton-Kellogg olefination as a key step in the synthesis …”
Section: Introductionmentioning
confidence: 96%
“…23,24 It was also demonstrated that α-oxo-dithioesters will undergo transesterification yielding thionoesters. 16,25 One notable use of this strategy is in the total synthesis of clostrubin, where the resulting thionoester was used in a Barton-Kellogg olefination as a key step in the synthesis. 26 Considering the above, we envisioned a streamlined synthesis of structurally diverse thionoesters could be achieved through a straightforward transesterification reaction from a starting methyl thionoester.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, all of these methods have been focused on constructing C2-carbon-substituted benzo­[ b ]­thiophenes. The reports on the synthesis of 3-hydroxybenzo­[ b ]­thiophene substituted by heteroatoms at the C2 position are limited to sulfur and nitrogen substitutions …”
Section: Introductionmentioning
confidence: 99%